Transforming Plastic Waste into Ecobricks : Case Study at MAS Al Hidayah, Serang Regency - Deni Sunaryo; Yoga Adiyanto; Dhany Isnaeni Darmawan; Hamdan Hamdan; Ahmad Firdaus (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
This community service activity aims to increase students' awareness of plastic waste management by utilizing the bottle ecobrick method. The community service was carried out on April 28, 2025 at the Al Hidayah Private Islamic High School (MAS), Sukaratu Village, Cikeusal District, Serang Regency. This activity was attended by 112 students from classes 11A, 11B, 11C, and 11D. The implementation of the activity was carried out by Lecturers Deni Sunaryo and Yoga Adiyanto from Serang Raya University (UNSERA), with the assistance of KKM students group 50-2025. The methods used include socialization, ecobrick making training, and student participation evaluation. The results of the activity showed that students were able to understand the concept of ecobricks and produce bottle ecobricks that can be used for various purposes. This activity is expected to be the first step in managing plastic waste in the school environment.